INFLUENCE OF SHANGHAI INTERACTIVE OUTDOOR ADVERTISING ON CONSUMER PSYCHOLOGY AND BEHAVIOR - LI, Zhenzhen; Nurul Ain Mohd Hasan (Dinasti Publisher, 2022)
This study explores the impact mechanism of interactive outdoor advertising on consumer psychology and behavior in Shanghai under the new media environment. In this study, qualitative research methods were used to observe and record the outdoor advertisements of Nanjing Road in Shanghai and the outdoor advertisements of Xujiahui subway station through field research. At the same time, the focus group interview method was used, and 4 groups were selected to conduct interviews with 10 people in each group. The interviewees are young people aged 18-35 who work and study in Shanghai. The research shows that the psychological motivation for consumers to participate in the interaction is that the interaction can satisfy their sense of association and presence, and the interaction affects the psychological effect and behavioral effect of advertising communication on consumers. The psychological level effect can arouse attention, generate interest, resonate and be satisfied to a certain extent. The behavioral level effect is reflected in the purchase behavior after being satisfied. This paper believes that in order to deepen the interaction with users, outdoor interactive advertising needs to strengthen creative design and use high-tech intelligent technology and create a scene-style media environment, so as to stimulate audience participation is the main method to improve the effect of advertising interactive communication.